Impregnated Zeolite as Catalyst in Esterification Treatment from High Free Fatty Acids Palm Oil Mill Effluent - Nugraheni, Ika Kusuma; Nuryati, Nuryati; Persada, Anggun Angkasa Bela; Triyono, Triyono; Trisunaryanti, Wega (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2021)
Although Palm Oil Mill Effluent (POME) can be used as a raw material for biodiesel production, the POME contains an excessive amount of Free Fatty Acids (FFA), necessitating a preliminary process and esterification. POME is degummed using phosphate acid and bleached with carbon active. Additionally, this study used KOH-impregnated zeolite to reduce FFA. The purpose of this study is to determine the effect of adding impregnated zeolite on esterification. POME was heated to 600C for 30 minutes, then degumming with 3 % of phosphate acid for 30 minutes, followed by bleaching with carbon active with a comparison ratio of 8:3 at 1000C for 1 hour, and finally, esterification with 3 percent impregnated zeolite from the POME weight at 600C for 4 hours. The analysis was conducted using titration methods to determine the FFA of each esterification. The data will be compared between zeolite and non-zeolite degumming, bleaching, and esterification. The results indicated that the most effective method for reducing FFA was degumming, bleaching, and esterification with zeolite.